Validating Self-Efficacy in the Multicultural Relationship Scale for High School Students - Yosef Yosef; Sri Sumarni; Siti Dewi Maharani; Iyakrus Iyakrus; Machdalena Vianty; Nurlina Nurlina; Aprezo Maba (Journal of Innovation in Educational and Cultural Research, 2026)
Despite the growing cultural diversity in secondary schools, validated instruments to measure student self-efficacy in multicultural relationships remain scarce within school counseling frameworks. This study developed and validated the Multicultural Relationship Self-Efficacy Scale (SMRS), a 20-item instrument grounded in Bandura's Social Cognitive Theory. A scale development design was employed with 745 high school students. Content validity was established via expert panel evaluation, and construct validity was examined through Confirmatory Factor Analysis (CFA). The results confirmed a four-factor structure—Cultural Respect, Supportive Relationship, Emotional Insight, and Mutual Acceptance—explaining 63.25% of the total variance. The scale demonstrated high internal consistency (). While model fit indices were within the marginal to acceptable range (?²/df = 2.11; SRMR = 0.064; CFI = 0.871; TLI = 0.850; RMSEA = 0.089), all standardized factor loadings were strong (??0.60), and discriminant validity was confirmed via HTMT ratios (0.61–0.78). These findings provide reliable empirical evidence for the SMRS as a diagnostic tool for school counselors to assess and enhance adolescent multicultural competence. By addressing a critical measurement gap, this study enables the development of targeted, culturally responsive interventions designed to foster inclusive school climates.